PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI MEDIA ULAR TANGGA BERBASIS KEARIFAN LOKAL PADA MATERI TELADAN PERUMUS PANCASILA DI KELAS III SDN DUKUH KUPANG 1/488 SURABAYA - Ringga Faishal Rasyid; Suhartono; Rachmani (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the improvement in students' learning motivation by applying the snake and ladder game media based on local wisdom in the Pancasila Education subject, specifically on the material of the Exemplary Figures of Pancasila Formulators, for third-grade students at SD Negeri Putat Jaya IV/380 Surabaya. The research was motivated by the observed lack of student engagement and motivation in monotonous learning activities. Using a Classroom Action Research (CAR) approach, this study was conducted in Class III-A, involving 27 students. Data were collected through questionnaires and direct observation during the learning process. The questionnaire responses were then analyzed using descriptive quantitative methods. The study was carried out in two cycles, each consisting of four stages. The results indicated a significant increase in student motivation, with an improvement of 11% from Cycle I (75%) to Cycle II (86%). This percentage demonstrates that the learning motivation of Class III-A students falls into the high category, affirming the effectiveness of the snake and ladder game media in enhancing engagement in Pancasila Education lessons.